Análise de atos e conceitos em português acadêmico - Rollsing, Lucas Zambrano (2018)
The present dissertation investigates academic Portuguese in some of its features that occur in the Postgraduate Program in Letters of the Pontifical Catholic University of Rio Grande do Sul (PPGL-PUCRS). We have set two objectives to be pursued: the primary one is to analyse pragmatically, via speech act theory (AUSTIN, 1990), acts conveyed in theses and dissertations in the PPGL corpora, in order to describe Portuguese according to its users’ intentions when using acts through written academic register; the secondary objective is to propose the beginning of a Linguistics Glossary through the extraction and analysis of concepts/terms, in accordance with the Intellectual Profile of Production (IPP) of PPGL. We have adopted Pragmatics as our epistemological thread, creating conditions thus to assume the speech acts theory, as well as the textual genre theory proposed by Bazerman (2009, 2015), as theoretical models to be followed, in combination with the model of research and teaching of the area of English for Academic Purposes (JORDAN, 1997; HYLAND, 2006). Therefore, our study corpus (CorpAcad) is constituted by the academic production of PPGL within the period of eleven years (2006-2016). Among the total amount of 206 texts we have 124 dissertations and 82 theses, whose area is solely from the Linguistics field of research. The corpus processing was made by the ExATO software (LOPES, 2012), which is an automatic extractor of relevant terms (noun phrases and verbal phrases), which traces an overview of a study corpus, by linguistic and statistic methods from the area of Natural Language Processing (LOPES; FERNANDES; VIEIRA, 2016). We tried to explicit in the use contexts (verbal concordances extracted by ExATO) of the 30 most representative verbs of CorpAcad the illocutionary forces probably conveyed by the authors in the moment of writing their texts, as a methodology to describe the speech acts. Thus, we have found chiefly expositive illocutionary acts, and, in lesser quantity, commissive illocutionary acts. Our methodology to start our future Linguistics Glossary followed the extractions steps of ExATO to identify relevant concepts/terms of a corpus, which gave us a list of the most representative concepts of the area of Linguistics in that period of time for the institution above mentioned. To make the list of concepts shorter and more accurate, in order to give us a sample to analyse, concepts concerning the area of Linguistics were chosen. These concepts went through a revision by different experts of different areas of Linguistics from PUCRS to categorize them as representative terms for their study areas. From that, a terminographic product was designed to be developed which could represent the IPP of the PPGL as a whole. At the moment, we have 148 terms listed to be inserted in the macrostructure of the glossary. Finally, we hope to bring some contributions to Portuguese teaching for academic purposes in the context of PUCRS, according to what Hyland (2006) suggests as a research-based language education, in order to provide practical applications for teaching, as activities that explore acts used in texts from Linguistics. In addition, we seek to offer a reference material for students of the PPGL and for the incoming ones that represent the postgraduate program to enhance their experience while masters and doctoral students.